Synthesis of vanadium-based oxides for rechargeable zinc ion battery cathodes - Sutanto, Leonardo (Nanyang Technological University, 2023)
Zinc ion batteries (ZIBs) have strong potential for usage as future energy storage technology because of their higher safety, cheaper production costs, and high material availability. Nevertheless, due to a scarcity of good cathode materials, current ZIB performance is still insufficient to meet rising energy consumption. In this experiment, we aim to achieve a porous nanostructure of Vanadium Oxide V2O5 @C; incorporated with Metal Organic Framework (MIL – 47(V)), as the cathode of ZIB battery. We utilized a conventional hydrothermal approach to synthesize MIL-47(V) which was then heated under argon atmosphere to obtain V2O5@C. The resulting ZIB battery performance was compared to that of the commercially used V2O5 cathode battery and excellent results was obtained. The V2O5@C cathode battery achieved a much higher specific capacity, and it can retain 80% of its capacity after 500 cycles, compared to only 26% capacity retention for the commercial V2O5 cathode. The V2O5@C cathode battery also showed better rate performance where it recorded a higher capacity when the current density was varied from 0.2 to 2.0 A g-1. The main reason for these improved characteristics was due to its high porosity nanostructure, which was proven from the SEM result. This V2O5 @C cathode structure has the potential to be used in long-term battery storage applications with high capacity and high-rate capability. Future recommendations include exploring ways on utilizing other types of MOF.